Kajian Sosiologi Sastra Robert Escarpit dalam Sistem Distribusi Penerbit Vanity Berbasis Daring B-STARS Publisher - Pratiwi, Anjar; Noor, Redyanto; Komariya, Siti (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study examined the network-based (online) distribution system of vanity publisher B-STARS Publisher (BSP), analyzed through the lens of Robert Escarpit's theory using a literary sociology research approach. Two main aspects, publication activities and distribution circuits, were encompassed in the analysis of the publisher's distribution system. The result of the analysis unveiled that BSP carried out work publication activities through Instagram social media after all the processes ended, ranging from selection, acceptance, and completion of the script. Furthermore, BSPs were categorized as popular circuits according to their distribution circuits. This category was based on five findings, namely (1) social media optimization as a distribution medium, (2) the non-limiting selection process, (3) the popularity of the manuscript primarily stems from widely recognized works on the Wattpad platform, (4) the characteristics of entertainment publishing works, not for intellectual purposes, and the publication is limitless, and (5) the economic or commodity side that sells BSP works predominantly in the genre of teen fiction (romance).